Association of Anthropometric and Lifestyle Parameters with Fitness Levels in Greek Schoolchildren: Results from the EYZHN Program - Arnaoutis, Giannis; Georgoulis, Michael; Psarra, Glykeria; Milkonidou, Anna; Panagiotakos, Demosthenes B.; Kyriakou, Dafni; Bellou, Elena; Tambalis, Konstantinos D.; Sidossis, Labros S. (Frontiers in Nutrition, 2018)
Objective The aim of the study was to evaluate physical fitness (PF) and identify its anthropometric and lifestyle determinants in a sample of Greek schoolchildren. Methods The study sample consisted of 335,810 schoolchildren (♂: 51.3%, 6–18 years old). Students’ anthropometric parameters and PF levels—assessed via the Eurofit test battery—were measured by trained physical education teachers and evaluated according to the available norms, while their lifestyle habits were assessed through a questionnaire. Results In all applied PF tests, students’ performance was negatively associated with the presence of obesity and central obesity, defined through international criteria for body mass index and waist to height ratio, respectively. According to multiple logistic regression analysis, the presence of overweight/obesity [odds ratio (OR): 4.43, 95% confidence interval (CI): 3.98–4.93], low adherence to the MD (KIDMED ≤ 3) (OR: 1.27, 95% CI: 1.09–1.48), and increased time spent in sedentary activities (>2 h per day) (OR: 1.16, 95% CI: 1.03–1.29) were positively associated with poor PF, after adjusting for age and sex. In contrast, for every 1 day increase in the weekly frequency of engagement in athletic activity, the probability of poor PF decreased by 26% (OR: 0.74, 95% CI: 0.72–0.77). In a similar model, the presence of central obesity emerged as an even stronger possible predictor of poor PF (OR: 5.20, 95% CI: 4.66–5.78), compared to the presence of general obesity. Conclusion Higher general or abdominal adiposity, as well as the adoption of a low-quality diet and a sedentary lifestyle, is strongly associated with low PF levels during childhood.